Body fat percentage, not early life experiences, predicts blood pressure in children in Utila, Honduras - Nicole Merullo; Jessica K. Hlay; Izabel Rodríguez-James; Caroline B. Smith; Brooke A. Rothamer; Madison A.C. Hönig; Michael R. Gaffney; Gabrielle Busi; Steven A. Arnocky; Aaron D. Blackwell; Carolyn R. Hodges-Simeon (Human Biology and Public Health, 2026)
Background: Elevated blood pressure distributes metabolic resources through the body, but can also cause pathology. Life history theory predicts that natural selection has acted on energy allocation, leading to strategic adjustments to psychosocial and energetic challenges posed by one’s environment. Objective: We test whether greater psychosocial challenges will necessitate increases in mean arterial pressure (MAP), predicting that greater social-economic-political-emotional (SEPE) stress is associated with higher MAP. We also test whether adiposity is positively associated with MAP. Methods: We measured the growth and development of 222 children longitudinally and cross sectionally from 2023-2025 in Utila, Honduras, where inhabitants experience varying levels of SEPE stressors. We measured standard anthropometrics, blood pressure, and morning salivary hormones. SEPE factors were collected from the primary caregiver at the time of consent to the study. Results: A Saint Nicolaus House Analysis network of associations showed a positive correlation between age adjusted MAP and body fat percentage (r = 0.29). Multiple regression analysis showed no significant relationship between SEPE factors and MAP (β = -0.86 and -0.78; p = 0.18 and 0.47) and instead showed a positive relationship between body fat percentage and MAP (β = 3.06; p = 0.01). Conclusion: Body fat percentage strongly predicts higher blood pressure, suggesting that metabolic status of children is an important predictor of potential cardiovascular risk. In contrast to our predictions, MAP appears relatively robust to variable exposures of stress among children in Utila. These findings underscore the need for cultural and location-specific studies of stress and blood pressure.